Is there a relationship between ICT development and human development?: an analysis of six major islands of Indonesia from 2012 to 2016 - Machfud, Alfi Khairiansyah; Kartiwi, Mira (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
This paper aim to describe the development of ICT in Indonesia by investigating the relationship between ICT development index (IDI) with the human development index (HDI), education index, expenditure index and the percentage of poor people between the six major islands of Indonesia. The Pearson Correlation analysis was used to explore the data collected for the period of 2012-2016. Among the interesting findings emerged from this study is the disparity of ICT development between the major islands in the western and eastern part of Indonesia. This paper also reveals that there are significant correlations between the IDI, HDI, education index, expenditure index and the percentage of poor people.